Pengaruh Rasio Profitabilitas Likuiditas dan Solvabilitas Terhadap Financial Distress Pada Perusahaan Manufaktur yang Terdaftar di Bei - Eka Yunindra, Andri; Merinda, Sinta; Hikmah, Nur (HUMAN: Journal of Social Humanities and Science, 2023)
ABSTRACT This study aims to determine the relationship between profitability ratios (ROA), liquidity ratios (CR) and solvency ratios (DER) to financial distress in basic industry and chemicals subsector manufacturing companies listed on the Indonesia Stock Exchange.  The sample in this study uses 24 corporate financial reports from population of 71 basic industry and chemicals subsector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. Data analysis techniques in this study using multiple linear regression analysis with data analysis tools in the form of ratio analysis using SPSS. The results of this study showed that profitability ratios (ROA), liquidity ratios (CR) and solvency ratios (DER) simultaneously  had a positive and significant effect on financial distress in manufacturing companies listed on the Indonesia Stock Exchange. The partial test results show that profitability ratios (ROA) have a positive and significant effect on financial distress, liquidity ratios (CR) have a positive and significant effect on financial distress, solvency ratios (DER) have a negative and significant effect on financial distress in basic industry and chemicals listed on the Indonesia Stock Exchange.